2015
DOI: 10.1002/oby.21247
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep duration and body mass index depends on age

Abstract: OBJECTIVE Sleep duration is associated with obesity and cardiometabolic disease. It is unclear, though, how these relationship differs across age groups. METHODS Data from the 2007–2008 National Health and Nutrition Examination Survey (NHANES) were used, including respondents aged 16+ with complete data (N=5,607). Sleep duration and age were evaluated by self-report and body mass index (BMI) was assessed objectively. Sleep duration was evaluated continuously and categorically [very short (≤4h), short (5–6h),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 36 publications
(40 reference statements)
11
56
2
4
Order By: Relevance
“…This is consistent with similar studies which report that older participants with longer sleep duration were likely to have lower BMI [55]. Sedentary time, however, was associated with higher BMI among both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with similar studies which report that older participants with longer sleep duration were likely to have lower BMI [55]. Sedentary time, however, was associated with higher BMI among both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…First, this relationship is dependent on age, with the strongest relationships among younger adults and U-shaped relationships more common in middle-aged adults. 47 Also, this relationship may be moderated by race/ethnicity, with stronger relationships between sleep and obesity among non-Hispanic white and black/African American adults. 24 …”
Section: Sleep Effects On Health and Longevitymentioning
confidence: 99%
“…20,21,24 The shape of the relationship between sleep duration and cardiometabolic risks may also vary in different age groups: Grandner and colleagues 21 found a linear relationship in younger adults and a U-shaped relationship in middle-aged adults. Aging is also considered as a risk factor for cardiometabolic dysfunction, and it is associated with increased inflammation and oxidative stress, as well as decreased antioxidant capacities, which may partially explain the higher cardiometabolic risk score seen in older adults in our study.…”
Section: Disparity Between the Sexes And Age Groupsmentioning
confidence: 99%
“…16 Previous studies have also found that several individual cardiometabolic risk factors are optimal among 7 to 8 h sleepers, 17,18 but poor sleep patterns and the prevalence of cardiometabolic risks are also higher in subgroups such as men, older adults, non-Hispanic Blacks, and smokers. [19][20][21][22][23][24][25] Further, the relationship between sleep duration and cardiometabolic risk may be U-shaped. 14,18 The relationship between sleep duration Sleep Health xxx (2017) xxx-xxx and a continuous measure of cardiometabolic risk may also be moderated by sex, age, ethnicity, and smoking status, which have been considered as confounding variables in previous studies, 4,13 but they may be significant moderators of the relationship.…”
Section: Introductionmentioning
confidence: 99%